Highly efficient photocatalytic reduction of CO2 to CO using cobalt oxide-coated spherical mesoporous silica particles as catalysts. Issue 77 (6th September 2019) - Fu, Zi-Cheng; Moore, Joshua T.; Liang, Fei; Fu, Wen-Fu
Abstract : Hybrid catalysts that cobalt oxide nanoparticles immobilized on outside surfaces of spherical SBA-15 presented unexpected photocatalytic activity towards CO2 -to-CO conversion. Abstract : New spherical hybrid materials as-synthesized by Cobalt oxide nanoparticles immobilized in situ on the outside surfaces of mesoporous silica particles exhibited highly efficient visible-light-driven catalytic performance towards CO2 -to-CO conversion. An average generation rate of CO of up to 25 626 μmol h −1 g −1 with a selectivity of 83.0% was achieved.